ESPOZ - AN ELECTRONIC SYSTEM SUPPORTING THE POLISH POLICE IN THE SEARCH FOR MISSING PERSONS - Anna Świerczewska-Gąsiorowska; Monika Porwisz; Paweł Olber (Revija za kriminologiju i krivično pravo)
The Police Academy in Szczytno has been carrying out a research project entitled "Development of a database and tools for semantic search for information and knowledge management in the area of missing persons and search for persons”, financed from the funds of the National Centre for Research and Development for national defence and security. The objective of the conducted research project is to prepare a database and a tool for semantic search for information and knowledge management in the area of missing persons and search for persons, as well as to equip the Polish Police with a technologically advanced tool for semantic and contextual search for information on standards, rules, good practices and specific patterns of behaviour in the area of searching for missing persons. The final effect of the mentioned research project is the eSPOZ system of searching for missing persons, which is described in the article.